스마트폰 환경에서 기사 읽기 습관 고려한 뉴스 추천 시스템 설계 및 구현 - 송특섭; Song, Teuk-Seob (한국정보통신학회논문지, 2014)
In this paper, we propose a news article recommendation system that reflects users' areas of interest and reading habits. Users can select interesting subject then our proposed system displays interesting articles above the other articles. Also the proposed system reflects users' dynamic interests using analyse of user's reading habits. The method of dynamic interest applies the different weight values from users simply clicking and reading entire articles. When users read articles from specific areas, the prosed system increases the weight of these specific areas using XML structure information. Hence users can read their articles of interest with ease. 본 연구는 스마트폰환경에서 사용자의 관심주제와 읽기습관을 분석하여 읽기 습관을 분석하여 관심 있는 뉴스기사를 추천 시스템을 제안하였다. 사용자가 직접 관심영역의 가중치를 정함으로서 관심주제의 기사를 우선적으로 보여 주어 사용자가 쉽게 관심기사를 읽을 수 있도록 하였다. 또한 사용자가 사회적으로 이슈가 되는 기사에 관심을 갖는 경우 이를 반영하기 위해서 단순히 기사를 클릭하고 읽지 않은 경우는 가중치를 낮게 설정하였으며, 기사를 끝까지 스크롤을 하고 기사를 끝까지 읽은 경우는 가중치를 높게 설정하였다. 특정 분야의 기사를 자주 읽은 경우는 XML의 구조정보를 사용하여 관심주제영역의 가중치를 높게 설정함으로써 관련분야의 기사를 우선적으로 볼 수 있도록 하였다.